Transjugular Intrahepatic Portosystemic Shunts for Acute and Chronic Portal Vein Thrombosis in Preparation for Liver Transplant - Novelli, Paula M.; Leo, Madeline; Orons, Philip D. (Digestive Disease Interventions, 2024)
The presence of portal vein thrombosis (PVT) in the pre-liver transplant patient can significantly impact waitlist, peri- and posttransplant outcomes, morbidity, and mortality. This article describes the pathophysiology of PVT and treatment options in patients with cirrhosis. It defines indications and rationale for placing transjugular intrahepatic portosystemic shunts, emphasizing technical details and risks in patients with nonneoplastic PVT awaiting liver transplantation.
Keywords: portal vein thrombosis; transjugular intrahepatic portosystemic shunt; liver transplant